Wayang Onthel Komunitas Old Bikers Velocipede Old Classic (VOC) Magelang - Figur Rahman Fuad (Universitas Gadjah Mada, 2016)
This article is a study on “Wayang Onthel”, a created by an Old-Bikers community calledVelocipede Old Classic (VOC) in Magelang, which utilizes the old bicycle spare partsas the wayang-making materials. The study focuses on “Wayang Onthel” as a work ofart. It is aimed at investigating the background of the creation of “Wayang Onthel”, itsshapes and characterization, as well as the relation between its forms and the identityof VOC community. This study employs sociology of art and aesthetics approaches,supported by the studies on creativity, identity, and semiotics. The creative process inthe making of this wayang resulted in such unique forms of wayang made of old bicycleparts being compiled and put together. The wayang’s characterization is obtained throughdifferentiating the use of spare parts and its arrangement patterns. The constraint ofspare parts in accommodating visual markers in characterizing the wayang could behandled by the addition of non-spare parts materials. Under semiotic perspective, theoverall shape of “Wayang Onthel” is an iconic symbol referring to human fi gures thewayang wants to portray. Meanwhile, in its forming elements lies an indexical symbolto maintain the “Onthel” image as the identity of VOC community.